Effect of inflationary expectations on stock market returns in Nigeria - Onyebuchi Iwegbu; Babatunde Wasiu Adeoye (Journal of Economic Studies, 2020)
This study examined the effect of inflationary expectations on stock market returns during the financial crisis era and the post-financial crisis era in Nigeria. The study built its argument using Fisher's effect to examine the objective. The study employed quarterly data spanning through the periods of first quarter 2007 till the fourth quarter of 2018. Using Autoregressive Distributed Lag estimation technique after the stationarity of the variables have been confirmed by ADF and its long-run stability confirmed by Bounds co-integration test, the study found that inflationary expectations are key determinants of stock market returns in Nigeria. The study concludes that stocks do not hedge over inflation as expectations built up by agents in the economy affects stock returns. The study, therefore, rejects the Fisher hypothesis for the case of Nigeria in the post-global financial crisis era.
Keywords: E31; E44; 330; Inflationary Expectations; Stock Market Returns; Autoregressive Distributed Lag Model (ARDL)